2019
DOI: 10.1111/jphp.12955
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical considerations in paediatrics with a view to the evaluation of orally administered drug products – a PEARRL review

Abstract: The biopharmaceutics tools for investigation of oral drug absorption in paediatrics need further development, refinement and validation. A combination of in vitro and in silico methods could compensate for the uncertainties accompanying each method on its own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 211 publications
(399 reference statements)
1
79
0
Order By: Relevance
“…Firstly, the chicken highest dose strength used in calculation of chicken D 0 is generally not controversial that was based on clinical observations (Chinese Veterinary Pharmacopoeia Commission, ). Secondly, our results showed a linear relationship between GI volume and body weight both in the fasted and fed state in chicken, it presented a similar trend in human which gastric volume in the fasted state is most often reported as a function of body weight (Guimaraes et al, ). At the same time, we found out a threefold change in GI volume after feeding in chicken, which leads to the same drug to be classified differently under fed or fasted.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Firstly, the chicken highest dose strength used in calculation of chicken D 0 is generally not controversial that was based on clinical observations (Chinese Veterinary Pharmacopoeia Commission, ). Secondly, our results showed a linear relationship between GI volume and body weight both in the fasted and fed state in chicken, it presented a similar trend in human which gastric volume in the fasted state is most often reported as a function of body weight (Guimaraes et al, ). At the same time, we found out a threefold change in GI volume after feeding in chicken, which leads to the same drug to be classified differently under fed or fasted.…”
Section: Discussionsupporting
confidence: 79%
“…The borderline for the low/high permeability must be defined when evaluating permeability (P app ) data from cell monolayer, and metoprolol is currently an acceptable and widely used marker for this purpose (Incecayir, Tsume, & Amidon, 2013;Zur et al, 2014), so metoprolol was used to be a reference standard for class in our research, and the classification results formed a good correlation with the absorption of drugs in chickens. LogP has been used for the permeability classification of canine BCS and pediatric BCS, and a LogP value greater than 1.72 as high permeability (Guimaraes et al, 2019;Papich, 2015), but the LogP only represents the lipophilic of drug molecules, and it ignores the enzymes and transporters inherent in human or animal organisms, thus, it is not surprising that predictions based only on LogP may frequently be in error, often because most drugs may be substrates for some transporter (Papich, 2015;Wu & Benet, 2010), such as some substrates (ciprofloxacin hydrochloride for P-gp and BCRP; sulfadiazine for P-gp) in our study (Zhang et al, 2018), which with a higher LogP value but a lower absorption in chicken. Moreover, we also discussed the role of pH on permeability class, and the result showed that pH has less influence on classification, except sulfamethoxazole, which was an acid drug (pKa 5.6), exhibits high class under pH 5.5 but low under pH 7.4, and it is well interpreted that acid drugs have higher permeability values at lower pH (Tolle-Sander, 2002;Yang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Medicine coadministration with vehicles is the most practiced manipulation strategy in paediatrics; however, no recommended Standardised coefficients corresponding to the variables studied for the logistic regression model constructed testing methodology or uniform criteria to define what is classed as globally acceptable for the different paediatric age groups (e.g. in terms of flavour, texture and composition) have been set to predict the possible impact of medicine coadministration with vehicles on drug product performance [6,11,32].…”
Section: Medicine Co-administration With Food and Drinks-from Regulatmentioning
confidence: 99%
“…These include: (i) seeking a licensed therapeutic alternative, (ii) importing products authorised in other countries (which can be costly, time-consuming, and often subject to strict regulations), (iii) compounding medicines within the pharmacy (i.e. preparing an unlicensed medicine to meet specific patient needs) or (iv) manipulating licensed dosage forms [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation